Institutional presence: Toward a further developed Community of Inquiry model integrating institutional functions in online and blended learning environment - Zhang, Wei; Zhu, Chang (Frontiers in Psychology, 2023)
In this research we examine the Community of Inquiry model and further develop the model by integrating a complementary institutional presence. For this purpose, a questionnaire including five presences and 73 questions was designed. In total, a response of 762 questionnaires from five universities were collected. Correspondingly, statistical analysis like factor analysis and structural equation model were conducted. The present paper is, duly, a quantitative investigation of the correlations between institutional presence and other presences in the new model as well. Finally, a further developed Community of Inquiry model that integrates institutional presence is generated. With a relatively large sample, the results meet the applicable requirements, indicating that the generated model is acceptable and fits well with the data.